2015
DOI: 10.1039/c5gc00194c
|View full text |Cite
|
Sign up to set email alerts
|

Biomanufacturing of CdS quantum dots

Abstract: A strain of Stenotrophomonas maltophilia is engineered to achieve size controlled synthesis of water soluble CdS quantum dots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 51 publications
(67 reference statements)
7
77
0
Order By: Relevance
“…For reference, our previous work (32) demonstrated that absorption peak maxima of 324, 334, and 344 nm correspond to biomineralized nanocrystallite sizes of 2.75 ± 0.68, 3.04 ± 0.75, and 3.36 ± 0.95 nm, respectively. Additionally, smCSEproduced CdS nanocrystals show similar quantum yield (1.8%) compared with synthesized CdS nanocrystals from S. maltophilia (2%) (32).…”
Section: Enzymatically Synthesized Cds Quantum Dots Are Monodisperse mentioning
confidence: 74%
See 1 more Smart Citation
“…For reference, our previous work (32) demonstrated that absorption peak maxima of 324, 334, and 344 nm correspond to biomineralized nanocrystallite sizes of 2.75 ± 0.68, 3.04 ± 0.75, and 3.36 ± 0.95 nm, respectively. Additionally, smCSEproduced CdS nanocrystals show similar quantum yield (1.8%) compared with synthesized CdS nanocrystals from S. maltophilia (2%) (32).…”
Section: Enzymatically Synthesized Cds Quantum Dots Are Monodisperse mentioning
confidence: 74%
“…We previously identified a putative cystathionine γ-lyase (smCSE) associated with the extracellular synthesis of CdS quantum dot nanocrystals by Stenotrophomonas maltophilia strain SMCD1 (32). Cystathionine γ-lyases (CSEs) are a class of enzymes that catalyze the production of H 2 S, NH 3 and pyruvate from L-cysteine, and the overexpression of which has been shown to precipitate cadmium sulfide (33).…”
mentioning
confidence: 99%
“…[14] It should be noted that extracellular production is preferable as it eliminates the requirement for cell lysis during harvesting, decreasing protein and other biomacromolecule contamination of the obtained nanocrystals. [24] However, the exact extracellular mechanism of CdS formation still remains unclear and requires further detailed investigation.…”
Section: Comparative Analysismentioning
confidence: 99%
“…[23] Formation of 3 § 0.2 nm-sized CdS nanoparticles was determined by HRTEM measurements. [24] In another study, [15] formation of extracellular CdS nanoparticles (5À20 nm in size) was achieved by the enzymatic reduction of sulphate ions by Fusarium biomass. Compared to our previous studies, [12,13] it could be concluded that all tested matrices (bacteria, plant culture and fungal mycelium) can be considered effective for extracellular, eco-friendly biosynthesis of CdS nanoparticles.…”
Section: Comparative Analysismentioning
confidence: 99%
“…12,13,15,20 Through identification and engineering of a cystathionine γ-lyase (smCSE) enzyme found associated with these nanocrystals, this procedure was simplified to a single enzyme approach for CdS biomineraliza-tion wherein we demonstrated that a single recombinant enzyme acts to both generate reactive sulfur via reduction of L-cysteine and template the formation of size controlled crystalline quantum dots. 20 This class of enzymes catalyze the formation of pyruvate, ammonia, and hydrogen sulfide from L-cysteine, providing the reactive sulfur precursor necessary for biomineralization.…”
Section: ■ Introductionmentioning
confidence: 99%